Mechanical Response Analysis of Battery Modules Under Mechanical Load: Experimental Investigation and Simulation Analysis. Issue 3 (16th December 2021) - Xi, Shoujun; Chang, Lijun; Chen, Wanyu; Zhao, Qiancheng; Guo, Yingfu; Cai, Zhihua
Abstract : Lithium‐ion batteries are widely used in the automotive, military, and energy storage fields, and the crash safety of batteries has attracted widespread attention. Herein, mechanical experiments are first carried out on a battery module (consisting of 18 650 cylindrical cells connected in parallel) and its components. The loading rates of the circular plates in the experiments are 1, 5, and 10 mm min −1 . Based on the experimental data, a finite‐element model of the module is developed and validated. The mechanical response of the module under static and dynamic conditions is then investigated through experiments and simulations. A parametric study is carried out to analyze the role played by the module holder in the mechanical response of the module. It is found that the presence of the module holder is effective in improving the distribution of the high‐pressure region under impact loading but causes a local increase in pressure peaks. This research work can provide a useful reference for the safe design of battery modules. Abstract : The mechanical response of the module under static and dynamic conditions is investigated through experiments and simulations. A parametric study is carried out to analyze the role played by the module holder in the mechanical response of the module. The research work can provide a useful reference for the safe design of battery modules.